GENERIC STRUCTURE POTENTIAL OF COURSE DESCRIPTION - Thanh, Ho Tuong; Tam, Nguyen Thi Minh (VNU Journal of Foreign Studies; Vol 37 No 1DO - 10.25073/2525-2445/vnufs.4659, 2021)
Generic Structure Potential (GSP), which is a “range of textual structures available within a genre” (Hasan, 1984, p. 79) was developed based on the need for a “generic structure” of a text to gain a comprehensive understanding of a genre (Halliday, 1978). Despite various research into different types of academic and promotional genres, there has been little attention given to the course description. This research seeks to unveil the GSP of course description and identify differences between formal course descriptions and online ones, analyzed based on a fourteen-element analytical framework. The findings revealed four more elements apart from those available in the original analytical framework. Most importantly, the course description was discovered to play the role of both informing and promotional, yet the former role is dominant. Regarding the difference between conventional and online descriptions, online ones were found to possess a higher number of promotional elements but still focus on informing students and promoting the course at the same time. The sequence of these elements seems to resemble the purchase decision-making process of customers significantly. On the contrary, the traditional description puts major emphasis on the informative purpose and shows negligence to the promotional aspects.